MÉTODO DE WALDORF Y SU INCIDENCIA EN LA TRIADA PEDAGÓGICA DE LOS ESTUDIANTES DE EDUCACIÓN BÁSICA - BUSTAMANTE PEREZ EDITH DE LAS MERCEDES (2024)
This research document mentions the methodological study of Waldorf and its impact on the pedagogical triad in basic education students. This work arises from the need to find alternative methodological proposals where each one manages to create useful learning throughout life. Its objective was to determine the pedagogical impact in relation to early childhood education, applying various research techniques which determined the scope of knowledge, an assessment of results was also carried out that were obtained through conclusions and recommendations, taking into account a qualitative and quantitative approach of an instrumental type. We worked in the bibliographic modality since most of the information was taken from reliable sources where field information was obtained by carrying out the research directly with the students. During the development of the field work, it was concluded that Waldorf education is a pedagogical and methodical offer dedicated to inclusive, humanistic and holistic education, since it takes into account the role of the subject in the everyday world, communicating with each other, and in this way to create unity while allowing children the freedom to explore and master learning.